Applying Translation Theory and Practice in Teaching - Didik Murwantono (Universitas Stikubank (UNISBANK) Semarang, 2009)
A basic premise of this article is that the institutional teaching of translation studies has evolved in the past years partly due to a growing connection between theory and teaching practice. The present article focuses on how translation process in theories and practices, on why theory is important for the teaching of the profession, and on the nature of theory. This discussion leads to a fundamental concern for the training of future translators for professional work. It is argued that translation trainees should be exposed to a variety of approaches to translation which are inspired by and connect to different theoretical schools so that students are in this way taught to be flexible in their approach to texts and will also learn theory in practical application. KEYWORDS: translation theories, translation practices, teaching, translation types, translator